2001
DOI: 10.1097/00005344-200104000-00010
|View full text |Cite
|
Sign up to set email alerts
|

KT3-671, an Angiotensin AT1 Receptor Antagonist, Attenuates Vascular but Not Cardiac Responses to Sympathetic Nerve Stimulation in Pithed Rats

Abstract: Effects of KT3-671 on vascular and cardiac sympathetic neurotransmission were investigated in pithed rats. The pressor response to spinal stimulation (5 Hz) of the pithed rat without the adrenals was approximately 75% of that with the adrenals. Guanethidine (8 mg/kg, i.v.) decreased by about 76% the pressor response to sympathetic stimulation in the pithed rat with intact adrenals and the guanethidine-resistant response was almost completely abolished by bilateral adrenalectomy. Therefore, the following experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Reflex tachycardia as a consequence of hypotension results from both increased sympathetic activity and decreased vagal one. We previously showed that angiotensin II receptor antagonists inhibited the facilitatory action of angiotensin II on the electrically stimulated norepinephrine release in perfused rat hearts (3), while they did not affect the tachycardia induced by sympathetic nerve stimulation in pithed rats (4). Although vagal efferent activity plays an important role in regulating heart rate change in a number of autonomic reflexes (5), there are few reports on effects of ACE inhibitors on the cardiac vagal neurotransmission.…”
mentioning
confidence: 99%
“…Reflex tachycardia as a consequence of hypotension results from both increased sympathetic activity and decreased vagal one. We previously showed that angiotensin II receptor antagonists inhibited the facilitatory action of angiotensin II on the electrically stimulated norepinephrine release in perfused rat hearts (3), while they did not affect the tachycardia induced by sympathetic nerve stimulation in pithed rats (4). Although vagal efferent activity plays an important role in regulating heart rate change in a number of autonomic reflexes (5), there are few reports on effects of ACE inhibitors on the cardiac vagal neurotransmission.…”
mentioning
confidence: 99%
“…In various hypertension models, KT3-671-induced blood pressure reduction also is not accompanied by a reflex tachycardia (15 -17). It has been reported that KT3-671 as well as losartan inhibited vascular but not cardiac sympathetic neurotransmission in pithed rats (11). In that paper, it showed that KT3-671 was approximately four times more potent than losartan in inhibiting vascular sympathetic neurotransmission.…”
Section: Discussionmentioning
confidence: 87%
“…KT3-671, a non-peptide ARB with no active metabolites (15), induced hypotension without causing reflex tachycardia in various animal models of hypertension (15 -17). Takata et al showed that neither KT3-671 nor losartan affected cardiac sympathetic neurotransmission in pithed rats (11). On the other hand, they showed that both ARB inhibited vascular sympathetic neurotransmission, and this vascular sympathoinhibitory effect by KT3-671 was more potent than that by losartan.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…KT3-671 does not affect normal renal function and reduces hypertension-induced pathological changes in the kidney (Amano et al, 1995). KT3-671 has recently been demonstrated to produce vascular sympathoinhibitory activity (Takata et al, 2001). KD3-671 (10(− 8), 10(− 7), 10(− 6) M) dose-dependently attenuated fibronectin production in isolated nephritic glomeruli from experimental rat model of mesangioproliferative glomerulonephritis.…”
Section: Nonpeptide At 1 Receptor Antagonists Under Clinical Trialsmentioning
confidence: 96%